MAIN DIRECTIONS OF IMPROVEMENT OF THE ECONOMIC, FINANCIAL AND SOCIAL SUBSYSTEMS IN THE REPUBLIC OF CHAD - Youssouf Ali Mahamat (Статистика и экономика, 2016)
The paper describes the main directions of development of the economy of the Republic of Chad, which is integrated into the world economy. Shows the structure of industrial production, resource potential and development prospects.